The effect of overcommitment and reward on muscle activity, posture, and forces in the arm-wrist-hand region - a field study among computer workers - Belinda HW Eijckelhof; Jennifer L Bruno Garza; Maaike A Huysmans; Birgitte M Blatter; Peter W Johnson; Jaap H van Dieën; Allard J van der Beek; Jack T Dennerlein (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVE: Office workers with high levels of overcommitment and low levels of reward are thought to be more prone to arm-wrist-hand symptoms, possibly through a higher internal physical exposure. The aim of this study was to examine the effects of high overcommitment and low reward on (i) forearm muscle activity, (ii) wrist posture and kinematics, and (iii) forces applied to computer input devices during computer work in an actual work setting. METHODS: We continuously measured wrist extensor muscle activity, wrist posture and kinematics, and forces applied to the keyboard and mouse for two hours during the daily work of 120 office workers with four different levels of overcommitment and reward (low-high, high-high, low-low, and high-low). RESULTS: Wrist velocities and accelerations in radial-ulnar direction were higher for workers with high compared to low overcommitment, while their wrist range of motion was similar, possibly indicating a higher work pace. Wrist extensor muscle activity and forces applied to the keyboard and mouse were not increased by high overcommitment and/or low reward. CONCLUSION: Overall, our findings provide little support for the proposed pathway of high overcommitment and low reward in the development of arm-wrist-hand symptoms through a higher internal physical exposure.